TINGKAT KEPEDULIAN SOSIAL PESERTA DIDIK DALAM KEGIATAN BELAJAR KELOMPOK: STUDI DESKRIPTIF PADA SISWA SMP X DAN SMA Y DI INDRALAYA - Avrila Aura Sayyidhina; Nayma Alia Putri; Indah Permata Sari; Nabila Dwi Putri; Ajeng Chandra Prameswari; Yusuf Hartono; Khadijah Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Developing students’ social awareness in group learning activities is crucial, especially for students at Junior High School X and Senior High School Y who are undergoing social and emotional development. However, there are still students who are not very active in collaborating, do not value their peers’ opinions, and tend to be individualistic in the group learning process. This study aims to describe the level of social awareness among students at Junior High School X and Senior High School Y in Indralaya during group learning activities. The study employed a quantitative approach using a descriptive method. The sample consisted of 60 students, comprising 31 students from Junior High School X and 29 students from Senior High School Y. Sampling was conducted using cluster random sampling. Data were collected through the distribution of a questionnaire using a Likert scale consisting of 35 statements. The research instrument was tested for validity and reliability using IBM SPSS Statistics, yielding a Cronbach’s Alpha of 0.853, indicating that the instrument has high reliability. The data were analyzed using descriptive statistics, including percentage calculations and categorization of scores. The results of the study indicate that the level of social concern among junior high and high school students generally falls into the moderate category. Among students at Junior High School X, the moderate category accounted for 81%, while among high school students, it was 72%. Additionally, students at High School Y had a higher percentage in the high category compared to students at Junior High School X. These findings suggest that students’ social concern still needs to be improved through.